POLARITY GUIDED EXTRACTION AND CHROMATOGRAPHIC IDENTIFICATION OF ACETOGENINS FROM Annona glabra L. LEAVES (Applied Biological Research, 2024)
Annona glabra L. (family: Annonaceae) is used as a traditional medicine  against several human infirmities, including cancer. Most of the members of  family annonaceae possess a unique class of natural product called  acetogenins. The present study was aimed to extract and fractionate the  acetogenins from the leaves of Annona glabra using the solvents of increasing  polarity, such as hexane, chloroform, ethyl acetate ethanol, and water. Solvents  with higher polarity such as ethyl acetate were found more effective in  extracting lactone-containing compounds as compared to the less polar  solvents. The quantity of acetogenins isolated from the A. glabra leaves was  estimated by lactone concentration test. LC-MS/MS screening showed the  presence of acetogenins in the samples with m/z values 596.9, 606.9, 679.8,  566.8, 550.85, 672.15, 672.15, 624.9 and 565.35. These findings open up  effective methods for separation and quantification of bioactive compounds. Further studies are to be focused on evaluating the efficacy of these compounds in pre-clinical and clinical trials, which may potentially contribute in  developing the novel therapeutic formulations.
Keywords: Acetogenin; column chromatography; lactone concentration test; LC MS/MS; polarity guided extraction